The role of MonoTotal in the primary diagnosis, prognosis and follow-up of patients with non-small cell lung cancer (NSCLC) - Prazakova, Marketa; Vrzalova, Jindra; Auge, Josep Maria; Safranek, Jarmil; Topolcan, Ondrej; Fuchsova, Radka; Spisakova, Marketa; Svobodova, Sarka; Holubec, Lubos; Pesta, Martin (Anticancer research, 2011)
BACKGROUND: A new cytokeratin tumor marker, MonoTotal was studied in lung cancer, the most common cause of cancer mortality worldwide. In non-small cell lung cancer (NSCLC) patients MonoTotal serum levels and their relationship to the tumor stage, histological subtype, early relapse and cancer-related death were evaluated. PATIENTS AND METHODS: MonoTotal serum levels were studied, using immunoradiometric assay in a group of 93 patients with newly diagnosed NSCLC undergoing radical surgery, and were compared to those with benign lung diseases. RESULTS: A diagnostic power of MonoTotal in distinguishing patients with NSCLC from benign lung diseases was demonstrated. Higher levels of MonoTotal were associated with advanced stages of squamous cell carcinoma and there was a positive correlation of marker with tumor size. Marker levels showed significant relation to disease-free survival and overall survival. CONCLUSION: MonoTotal seems to be a potentially very interesting serum marker that, in conjunction with other clinical data, might be used for monitoring of patients with NSCLC.
Keywords: následné studie; Prognosis; nádory plic; nemalobuněčný karcinom plic; prognóza; Humans; Lung Neoplasms; Carcinoma, Non-Small-Cell Lung; Follow-Up Studies; lidé